2020
DOI: 10.1155/2020/6970823
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Steroid Cell Tumor (Not Otherwise Specified): A Case Report of Ovarian Hyperandrogenism

Abstract: Steroid cell tumors (SCTs) (not otherwise specified (NOS)) are rare sex cord-stromal tumors of the ovary. These are associated with hormonal disturbances resulting in menstrual bleeding patterns and androgenic effects. We report the case of a 36-year-old female presented with hirsutism, signs of virilization, and elevated androgen levels. Transvaginal ultrasound showed a solid-appearing right ovarian mass. She underwent fertility-sparing surgery with a laparoscopic left oophorectomy. Histological examination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Some studies even claim that these markers could facilitate the differential diagnosis of ovarian adenocarcinoma. 11,14 This correlates with the described case, as even after disease relapse, tumor markers remained within the normal range.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies even claim that these markers could facilitate the differential diagnosis of ovarian adenocarcinoma. 11,14 This correlates with the described case, as even after disease relapse, tumor markers remained within the normal range.…”
Section: Discussionsupporting
confidence: 90%
“…Hyperandrogenic tumors may also be associated with paraneoplastic manifestations, such as hypercalcemia, erythrocytosis, or ascites. 11 However, about 25% of patients with SCTs may have atypical presentations, without any symptoms of virilization. In these cases, the diagnosis is usually made postoperatively after histopathological verification.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid cell tumors have been described as a very rare (<0.1%) class of ovarian neoplasm, with SCT-NOS, comprising between 50% and 60% of the subtypes within this category. 9 - 11 A review of the literature demonstrates that most patients present in their 30s to 40s with rapidly progressive hyperandrogenism leading to virilization., 2 - 4 , 9 - 11 though this tumor has also been described in postmenopausal women. 12 The typical hormone profile of SCT-NOS, has been consistently described as elevated 17-OHP, elevated testosterone, and normal DHEA-S. 9 , 10 Scheker and colleagues have also identified increased expression of enzymes (namely AKR1C3) associated with ovarian steroidogenesis in SCT-NOS, suggesting a potential biomarker and a more specific mechanism for hyperandrogenism with ovarian origins.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used imaging techniques for this type of tumor are ultrasound and MRI. As demonstrated by transvaginal ultrasound, ovarian steroid cell tumors are solid tumors with a hypo-/iso-echoic, homogeneous or heterogeneous texture (10,(15)(16)(17), characterized by abundant blood flow signals (18). On MRI, steroid cell tumors appear heterogeneous and as medium-intensity solid mass interspersed with small cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Certain tumors may be so small that they may not be diagnosed even after careful radiological scrutiny ( 17 , 20 ). In the case of the present study, no obvious mass was observed on the right ovary on MRI.…”
Section: Discussionmentioning
confidence: 99%